Ответы и объяснения

  • Участник Знаний
2014-03-10T07:47:31+00:00
cos2x - 2sin2x + 2 = 0

воспользуемся 3 формулами
cos2x = cos^2x - sin^2x
sin2x = 2sinx*cosx
1 = sin^2x + cos^2x

Получим следующее
cos^2x - sin^2x - 2*2sinxcosx + 2cos^2x + 2sin^2x = 0
получили однородное триг. ур. второй степени
sin^2x - 4sinx*cosx + 3cos^2x = 0 /: cos^2x≠0
tg^2x - 4tgx + 3 = 0
Пусть tgx=t, t ∈ ( - беск; + беск), то
t^2 - 4t + 3 = 0
( t - 1)( t - 3) = 0
t = 1 ===> tgx =1 ===> x = pi/4 + pik, k ∈Z
t = 3 ===> tgx = 3  ===> x = arctg(3) + pik, k ∈Z

ОТВЕТ:
x = pi/4 + pik, k ∈Z
x = arctg(3) + pik, k ∈Z